2006
DOI: 10.1002/chin.200638105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Naphthofuranquinones with Activity Against Trypanosoma cruzi.

Abstract: New naphthofuranquinones (II), (III), (IV) and (VI) are synthesized from 2-hydroxy-3-allylnaphthoquinone (I) or nor-lapachol (IV) and evaluated for their trypanocidal effects. All compounds show marked activity and inhibit epimastigote proliferation. -(SILVA, R. S. F.; COSTA, E. M.; TRINDADE, U. L. T.; TEIXEIRA, D. V.; PINTO, M. D. C. F. R.; SANTOS, G. L.; MALTA, V. R. S.; DE SIMONE, C. A.; PINTO, A. V.; DE CASTRO*, S. L.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…A similar activity increase against T. cruzi has been reported in studies with culture epimastigote forms treated with bromine furanquinones [102]. This study also showed that quinones 25a, 25b and 26a inhibit epimastigote proliferation [103]. The aminated compound 26a presents a high trypanocidal activity and the lack of previous reports in the literature on amino naphthofuranquinones has stimulated the synthesis of compounds with aminated groups linked to the furane ring.…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…A similar activity increase against T. cruzi has been reported in studies with culture epimastigote forms treated with bromine furanquinones [102]. This study also showed that quinones 25a, 25b and 26a inhibit epimastigote proliferation [103]. The aminated compound 26a presents a high trypanocidal activity and the lack of previous reports in the literature on amino naphthofuranquinones has stimulated the synthesis of compounds with aminated groups linked to the furane ring.…”
Section: Methodssupporting
confidence: 52%
“…De Castro et al [103], described for the first time in the literature the synthesis of 25b and 26b and, although the synthesis of 25a had been described long time ago, there is no report about its biological activity. In vitro assays with bloodstream forms of T. cruzi resulted in to IC 50 /24 h values for 25a, 25b and 26a in the range of 157-640 μM, while the corresponding value for crystal violet, the standard compound, was 536 ± 3 μM (Fig.…”
Section: Methodsmentioning
confidence: 98%
“…Three naphthoimidazoles (N1-N3) derived from b-lapachone were the most active derivatives on the parasite (Pinto et al, 1997;Neves-Pinto et al, 2000Moura et al, 2001Moura et al, , 2004Silva et al, 2006Silva et al, , 2008a. These naphthoimidazoles were also effective on intracellular amastigotes and epimastigotes, in this latter form inhibiting DNA duplication (Menna-Barreto et al, 2005.…”
Section: Naphthoquinones and Derivativesmentioning
confidence: 95%
“…From C-allyl lawsone three naphthofuranquinones (Q1-Q3) were synthesized, which were active on trypomastigotes, epimastigotes and intracellular amastigotes, presenting low toxicity to the host cells (Silva et al, 2006). The ultrastructural evaluation of treated epimastigotes demonstrated severe mitochondrial damage, with loss of internal membrane, formation of concentric membrane structures and organelle swelling (Fig.…”
Section: Naphthoquinones and Derivativesmentioning
confidence: 99%
“…Naphthoquinones have been found to be cytotoxic towards various human cancers including ovarian, breast, lung and cervical cancers lines (Bonifazi et al, 2010;da Silva Júnior et al, 2010), with many compounds displaying IC 50 values of -5 mM. This group of compounds has also been shown to exhibit trypanocidal activity (Ferreira et al, 2006;Silva et al, 2006;da Silva Júnior et al, 2008) and antiplasmodial activity. A group of aminonaphthoquinones was tested in P. falciparum (clones W2 and D6) growth inhibition assays, with one of the aminoquinones displaying higher potency than chloroquine towards the W2 clone (Kapadia et al, 2001).…”
Section: Discussionmentioning
confidence: 96%